Exploration of factors affecting changes in student learning behavior: A systematic literature review - Mutiawati Mutiawati; Mailizar Mailizar; Rahmah Johar; Marwan Ramli (Institute of Advanced Engineering and Science, 2023)
The general learning behavior has a major impact on the psychological and mental adjustment of students to learn. Therefore, this study reviews relevant studies on the factors causing changes in student learning behavior. The review used PRISMA, so several stages were carried out to filter and collect relevant information. The results of the synthesis revealed 19 broad factors influencing student learning behavior. Furthermore, these factors can be seen in more detail in four main groupings: i) Student learning behavior in the classroom; ii) Student learning behavior outside the classroom; iii) Student learning motivation; and iv) Student learning behavior results. Student learning behavior in the classroom is influenced by motivation, reflection, learning satisfaction, and learning activities. Meanwhile, student learning behavior outside the classroom is influenced by technology, independent learning abilities, learning resources, learning environment, and students’ internal conditions. The final result showed that students with a positive learning environment consistently acquire good knowledge in achieving learning objectives. There are many challenges in forming good student learning behavior. Therefore, this study benefits the education experts, counselors, teachers, parents, and the learning environment by increasing student motivation and satisfaction in learning to minimize the negative impact of changes in student learning behavior.